Log-Kumaraswamy distribution: its features and applications - Ishaq, Aliyu Ismail; Suleiman, Ahmad Abubakar; Daud, Hanita; Singh, Narinderjit Singh Sawaran; Othman, Mahmod; Sokkalingam, Rajalingam; Wiratchotisatian, Pitchaya; Usman, Abdullahi Garba; Abba, Sani Isah (Frontiers in Applied Mathematics and Statistics, 2023)
This article aims to present a new continuous probability density function for a non-negative random variable that serves as an alternative to some bounded domain distributions. The new distribution, termed the Log-Kumaraswamy distribution, could faithfully be employed to compete with bounded and unbounded random processes. Some essential features of this distribution were studied, and the parameters of its estimates were obtained based on the maximum product of spacing, least squares, and weighted least squares procedures. The new distribution was proven to be better than traditional models in terms of flexibility and applicability to real life data sets.